Prototype Multisensor Fire Detection Based on Internet of Things (IoT) - Mohamad Rofiq; Didik Aribowo; Desmira Desmira (Jurnal Inovasi Pendidikan dan Sains, 2025)
Fire is an unpredictable disaster and often has a significant impact on human life, both materially and non-materially. Fires are often only detected when they have grown large, causing unavoidable losses. Various factors such as short circuits in the electrical network, LPG gas leaks, and human negligence are the main causes of fires. In this situation, an early detection system is needed that can provide real-time information to minimize the impact of fires. This study aims to design a prototype of a multisensor fire detector based on the Internet of Things (IoT) that integrates a fire sensor, MQ-2 gas sensor, and DHT22 temperature sensor with the Blynk application to provide real-time notifications. This system is also equipped with an LCD as a warning display and a buzzer as an alarm. The prototype has been tested in a controlled environment simulating fire conditions, including gas leaks and high temperatures, with multiple trials to verify its reliability. The results show that the system can detect fires at a maximum distance of 100 cm, hazardous gas concentrations starting from 600 ppm, and temperatures exceeding 35°C as the fire detection threshold. However, performance may be affected in environments with high humidity levels or areas with poor network connectivity. With effective hardware and software integration, the prototype helps users detect potential fires early and minimize the risk of fire losses